The Influence Of Work Environment, Individual Characteristics, Discipline And Leadership Style On The Performance Of Subbidprovos Bispropam Polda Kepri - Tanjung, Rona; Mira Yona; Jeffi Mutiara; Elaria Mirhanda (Sekolah Tinggi Ilmu Ekonomi Bentara Persada, 2024)
Disciplinary violations that are still occurring in the Riau Islands Police Subbidprovos Bidpropam, which has tagging responsibility in its work, namely managing the orderliness of every member of the police, is currently an obstacle. This study aims to determine the effect of the Work Environment, Individual Characteristics, Discipline, and Leadership Style on the Performance of the Riau Islands Regional Police Bidpropam Subbidprovos. The population in this study were all members of the Riau Islands Police Subbidprovos Bidpropam, totaling 88 people. The sampling technique was carried out using the Saturated Sampling Jenuh. Data were obtained using a questionnaire instrument that had been tested for validity and reliability. The results showed that: there was an influence of the work environment, individual characteristics, discipline, and leadership style on the performance of the Riau Islands Police Subbidprovos Bidpropam, this can be seen from the results of the work environment, namely tcount thitung (4.395) > ttabel (1.988), df = 83. Individual characteristics is tcount thitung (-574) < ttabel (1.988), df = 83. Discipline is tcount yaitu thitung (3.517) > ttabel (1.988), df = 83. Leadership style is tcount thitung (2.408) > ttabel (1.988), df = 83.